Determinan Kualitas Laporan Keuangan Koperasi Pegawai Negeri: Pengujian Peran Moderasi Tingkat Penerapan Sistem Pengendalian Internal - Ni Ketut Siti Ardianti; Made Aristia Prayudi (Vokasi : Jurnal Riset Akuntansi, 2020)
The purpose of this research is to empirically prove the influence of understanding of cooperative accounting based on SAK-ETAP, and the use of accounting information systems on the quality of financial statements of KPN and to determine the effect of internal control systems in moderating the relationship between understanding of cooperative accounting based on SAK-ETAP, and the use of systems accounting information. The research method used is a causal quantitative method, the type of data used is primary data, using the instrument method in the form of a questionnaire. Samples were obtained using the purposive sampling method. Data analysis techniques used were t test and interaction test (Moderated Regression Aanlysis). The results of this study indicate that: (1) understanding of cooperative accounting based on SAK-ETAP has a positive and significant effect on the quality of the KPN financial statements, (2) the use of accounting information systems has a positive and significant effect on the quality of the KPN financial statements, (3) the system internal control strengthens the positive relationship between SAK-ETAP-based cooperative accounting understanding and the quality of the KPN financial statements, (4) the internal control system strengthens the positive relationship between the utilization of accounting information systems and the quality of the KPN financial statements.